Plan de Educación Ambiental para el Manejo de Residuos Sólidos Generados en Diferentes Instituciones Educativas del Cantón Loja - Leiva Guzmán, Alex Dario (2018)
Abstract:The generation and management of solid waste cause problems in several ambits such as health, environment, urban development among others. The change of attitude and behavior of people in front of issues of environmental problems would favor to diminish the pressures on the environment. The present work was carried out in three institutions in the city of Loja. A diagnosis was made about the weaknesses in the generation and management of waste, through the application of surveys to students and on-site observation visits. It was determined that the organic residues that are most generated are the remains of food with 76.59%; waste of academic practices 21.10% and other 2.31%; meanwhile, the inorganic ones, the most generated is paper / cardboard with 64.16%; 19.65% plastic; bathroom waste 11.56%; 2.89% glass; batteries 1.16%, cans 0.87%. Supported in these results, the Environmental Education Plan was proposed, which seeks participation, education and awareness on the part of the students, through various programs, with the purpose of reducing the negative environmental impacts and social in the respective institutions in which it will applied.